Variation in circadian rhythms is maintained among and within populations in Boechera stricta. (13th February 2016) - Salmela, Matti J.; Greenham, Kathleen; Lou, Ping; McClung, C. Robertson; Ewers, Brent E.; Weinig, Cynthia
Abstract: Circadian clocks have evolved independently in all three domains of life, and fitness benefits of a functional clock have been demonstrated in experimental genotypes in controlled conditions. Still, little is known about genetic variation in the clock and its fitness consequences in natural populations from heterogeneous environments. Using Wyoming populations of the Arabidopsis relative Boechera stricta as our study system, we demonstrate that genetic variation in the clock can occur at multiple levels: means of circadian period among populations sampled at different elevations differed by less than 1 h, but means among families sampled within populations varied by as much as 3.5 h. Growth traits also varied among and within populations. Within the population with the most circadian variation, we observed evidence for a positive correlation between period and growth and a negative correlation between period and root‐to‐shoot ratio. We then tested whether performance tradeoffs existed among families of this population across simulated seasonal settings. Growth rankings of families were similar across seasonal environments, but for root‐to‐shoot ratio, genotype × environment interactions contributed significantly to total variation. Therefore, further experiments are needed to identify evolutionary mechanisms that preserve substantial quantitative genetic diversity in the clock in this and other species. Abstract : Circadian clocks characterise all three domains of life and exhibit genetic variation in various study systems. Still, little is known about the distribution of such diversity at different levels, e.g. among and within natural populations, in the wild. Using populations of the Arabidopsis relative Boechera stricta as our model system, we demonstrate substantial quantitative genetic diversity in the clock among and especially within populations in south‐eastern Wyoming and provide evidence on its adaptive significance. Our data are consistent with the hypothesis that circadian cycles near 24 hours may enhance some aspects of growth while reducing others, which along with environmental heterogeneity could act as a mechanism that maintains clock variation.